High internal phase emulsions stabilised by supramolecular cellulose nanocrystals and their application as cell-adhesive macroporous hydrogel monoliths. Issue 14 (24th March 2017) - Liu, Sa; Jin, Min; Chen, Yunhua; Gao, Huichang; Shi, Xuetao; Cheng, Wenhua; Ren, Li; Wang, Yingjun
Abstract : Macroporous composite hydrogel monoliths constructed from supramolecular cellulose nanocrystals stabilised HIPE template demonstrate exciting biocompatibility and cell adhesion. Abstract : Nanosized celluloses are attractive building blocks to generate hierarchically advanced materials and have been gradually explored in emulsion applications. Here we report a high internal phase emulsion (HIPE) prepared by using supramolecular cellulose nanocrystals (CNCs) as Pickering stabilisers via one-step emulsification, and interconnected macroporous hybrid hydrogels were produced by utilizing this HIPE as a template. A quadruple hydrogen bonding moiety 2-ureido-4[1 H ]-pyrimidone (UPy) was firstly grafted onto the surface of cellulose nanocrystals through simple free radical polymerization. The polymer grafting was confirmed by elemental analysis and thermogravimetry. The UPy modified CNCs (CNC-UPy) exhibited superior emulsion stabilising ability compared to the pristine CNCs, and the oil-in-water emulsions with an internal phase volume ratio of 80% showed good long-term stability. The properties of resulting macroporous polyHIPE hydrogels, such as swelling behaviours, porous structures and mechanical strength, were investigated on the dependence of CNC-UPy concentrations. In addition, the macroporous hybrid hydrogel exhibits excellent cytocompatibility and cell adhesion as demonstrated by mouse bone mesenchymal stem cell (mBMSC) culture. With these promising properties, the developed hydrogels demonstrate great potential as active biological scaffolds for tissue engineering.